Bidang Garapan Administrasi dan Manajemen Sekolah Atau Madrasah - Mardiyah Mardiyah; Habib Muhammad Bahaus Suruur; Mujia Yahdillah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
In order to raise the standard of education, human resource management is always linked to management and administration of education. Management can take the shape of agreements and guidelines, or it can take the form of a procedure for maintaining records. It is impossible to isolate educational management and administration from its various facets. We talk about the extent of education management and management procedures in this context. The purpose of management is to streamline organizational work systems and ensure successful and efficient implementation. This essay attempts to clarify how management is being implemented in the education sector, with a focus on the components and domains of school administration work. The